Rewetting of Hot Vertical Surfaces by a Falling Liquid Film. Issue 7 (4th April 2015) - El‐sayed Mosaad, Mohamed
Abstract : In this work, a transient heat conduction model is developed for rewetting a hot wall surface by a falling liquid film. In the model, the heat conduction in the rewetted wall is assumed to be two‐dimensional. Convection heat transfer from the hot surface to rewetting fluid is considered negligible in the dry surface region ahead of the wet front. The numerical solution indicates that the rewetting process is mainly controlled by two‐dimensional heat conduction in the rewetted wall, even for the walls of low Biot number, especially at low initial temperatures. The effects of Biot number and initial wall temperature on the rewetting velocity are investigated. Comparison of the results with previous studies is presented.